PERBAIKAN JARAK TANAM LEGOWO 2:1 UNTUK MENINGKATKAN PERTUMBUHAN PADI VARIETAS INPARI Ir. NUTRIZINC DI BALAI STANDAR INSTRUMEN PERTANIAN (BPSIP), NUSA TENGGARA TIMUR - Emil Sainal Selan; Abdonia W. Finmeta; Nardi M. Leo; Kristina Lako (CV. ADIBA AISHA AMIRA, 2025)
Rice production can be increased through improvements in the planting system and the number of seeds per planting hole. The objective of this study was to determine the effect of planting distance in a 2:1 legowo planting system. The study was conducted at BPSIP Naibonat NTT from March to April 2024. The experimental design used was a Randomised Block Design (RBD) with a legowo 2:1 planting system, consisting of 3 treatments: 20 x 10 x 40 cm (j1), 20 x 15 x 40 cm (j2), and 20 x 20 x 40 cm (j3), each with 3 replications, with each replicate consisting of 3 treatments, resulting in 9 treatments in total. The results showed that the 2:1 legowo planting distance with a spacing of 20 x 20 x 40 cm improved rice plant growth and yield, with the best effect on plant height at 103 cm, panicle length at 23.5 cm, and the best effect on plant height at 103 cm, number of tillers per clump 17.33 tillers, between the legowo 2:1 planting distance which was the best for the plant height parameter with a value of 103 cm, number of tillers per clump with an average of 17.33 tillers, number of productive tillers per clump 16.33 tillers, and number of grains per panicle with an average of 137.33 grains.